Propostas prático-pedagógicas para o ensino do gênero reposta nos anos finais do ensino fundamental - CUNHA, Deiseane Campos da (2023)
The objective of this study was to provide 9th grade students with knowledge about the response genre, and through training activities, make them proficient readers and producers. The proposals were divided into 3 axes: a) strategies for the use of argumentation; b) textual articulators and finally c) working cohesion and coherence through revision and rewriting. These proposals were applied in a larger elementary school in the municipality of Tomé-Açu-PA. The diagnostic and formative evaluation were applied in the third axis and obtained results that will contribute to the improvement of teachers in terms of teaching-learning.